Hashimoto's encephalitis as a differential diagnosis of Creutzfeldt-Jakob disease. Issue 2 (1st February 1999) - Seipelt, M; Zerr, I; Nau, R; Mollenhauer, B; Kropp, S; Steinhoff, B J; Wilhelm-Gössling, C; Bamberg, C; Janzen, R W C; Berlit, P; Manz, F; Felgenhauer, K; et al.
Abstract : OBJECTIVES: During an epidemiological study of Creutzfeldt-Jakob disease in Germany, Hashimoto's encephalitis was encountered as a differential diagnosis, which has not yet been described in this context. METHODS: The symptoms and findings of seven patients who fulfilled the criteria for "possible"Creutzfeldt-Jakob disease are presented. RESULTS: A Hashimoto's thyroiditis with antibodies against thyroglobulin or thyroid peroxidase, or both and a hypoechoic thyroid ultrasonogram were found in all cases. Analysis of CSF disclosed an increased leucocyte count in three patients, and a raised CSF:serum concentration ratio of albumin (QAlb) in four patients. The 14–3–3 protein, typical of Creutzfeldt-Jakob disease, could not be detected in any of our patients. No periodic sharp wave complexes, which are typical of Creutzfeldt-Jakob disease, were detected on EEG in any of the cases. By contrast with Creutzfeldt-Jakob disease, which leads to death within a few months, the patients with Hashimoto's encephalitis often recover quickly when treated adequately. All the patients improved after administration of corticosteroids. CONCLUSION: The clinical symptomatology of both diseases may be very similar: dementia, myoclonus, ataxia, and personality change or psychotic phenomena are characteristic symptoms.